The Keto-Enol Tautomerism of Curcumin and Some 4-substituted Curcumin Derivatives : A Theoretical Study Based on Computational Chemistry Approach - Enade Perdana Istyastono; Supardjan A. Margono; Harno Dwi Pranowo (Indonesian Journal of Pharmacy, 2003)
Heat formation (DHf) for the enol and diketo tautomers of curcumin and some 4-substituted curcumin derivatives has been studied using semiempirical AM1 quantum-chemical calculations. The calculations on curcumin, 4-methylcurcumin, 4-ethylcurcumin, 4-npropylcurcumin, 4-isopropyl-curcumin, 4-n-butylcurcumin, and 4-benzylcurcumin showed that the more steric hindrance resulted from the subtituents, the more stable they were in the form of diketo tautomers than enol tautomers. Whereas, calculations on 4-phenylcurcumin, 4-(o-methoxyphenyl)-curcumin, and 4-(p-methoxyphenyl) curcumin showed that though steric hindrance influenced the keto-enol tautomerism, they were found more stable in the form of enol tautomers. This phenomenon was estimated to be related with conjugation effect of the aromatic groups with the enol moiety of the main bone structure.Keywords : 4-Substituted curcumin, the keto-enol tautomerism, AM1, semiempirical calculations.